La flexibilidad en la arquitectura como estrategia de apropiación del espacio habitable por parte de los habitantes de calle (2023)
Over time there has been an increase in the way in which street dwellers take over the city to inhabit, and how these people create their own architecture, but nevertheless I know how these people do not have a direct relationship with the appropriation of a space worthy of housing, to be able to meet their habitability problem, as well as their way of reintegrating into the city or society.